Solitary keratoacanthoma of the lip vermilion: case report and comprehensive review of literature - Silva, Aneliza de Fatima Moraes da; Damante, José Humberto; Taveira, Luiz Antônio Assis; Tjioe, Kellen Cristine (Journal of Oral Diagnosis, 2019)
Solitary keratoacanthoma (S-KA) is a benign epithelial proliferation that affects the sun-exposed skin of elderly. It presents rapid growth often followed by spontaneous remission. S-KA clinical and microscopic features are very similar to the squamous cell carcinoma’s (SCC) and differentiating them can be a challenge. S-KA involving the lip is rare and frequently is managed as SCC, leading to overtreatment. Despite of few investigations aiming at differentiate S-KA and SCC are available, there is no compilation of case reports of lip S-KA. Thus, our aim was to conduct a comprehensive review of the literature and report a case of lip S-KA. The review was conducted until 2016 and only 21 cases were found. Lip S-KA was more common in elder man, lower lip, and most of them were asymptomatic. The lesions measured 16.7mm on average with duration of approximately 12 weeks. The most performed treatment was excisional biopsy of lesion despite of the self-healing potential of the lesion.